Forensic science : the basics - Siegel, Jay A.; Mirakovits, Kathy (CRC Press, 2010)
Featuring case studies, photographs, and exercises, this book provides information the non-scientist needs to be able to understand and utilize the research approaches that forensic science can offer. It is suitable for detectives, journalists, prosecutors, defense attorneys, and other non-science professionals